Model Multistatus Markov untuk Asuransi Kesehatan - Amritha, Yadhurani Dewi; Dananjaya, Made Wira Putra; Windaryani, I Gusti Agung Istri (Jurnal Matematika; Vol 14 No 2 (2024), 2024)
Death is a certainty happen at any time. It will enhance financial risk and disrupt financial stability, therefore insurance was developed to protect financial stability if it happens. This study aims to determine the transition probability matrix and health insurance premiums using a discrete-time Markov model for three states: healthy, sick, and deceased, with the assumption of a constant interest rate. In the Markov method, each condition has a probability of transition to another condition which provides more systematic way to estimate long-term risk by considering the possibility of various health conditions or status of the insured. It is assumed that the probability of illness to health is the percentage of the number of sick customers who do not file a claim for illness again to the number of customers who file a claim for illness plus ? = 0.05, 0.001 and 0.1. The results of the study showed that a person aged 17 years is entitled to health insurance benefits during a 5-year coverage period in the form of funds of Rp 50,000,000.00 if the insured dies or a maximum treatment benefit of 50% of the death benefit or according to the value of the receipt given by the doctor. In this case, the inpatient benefit value is given at Rp10,000,000.00, then the premium that must be paid per year with the assumption that the interest rate is a rent for the use of money for a certain period of time with an interest of 5% is Rp230,878.00215.